2009
DOI: 10.1038/ng.286
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiles in monozygotic and dizygotic twins

Abstract: Twin studies have provided the basis for genetic and epidemiological studies in human complex traits. As epigenetic factors can contribute to phenotypic outcomes, we conducted a DNA methylation analysis in white blood cells (WBC), buccal epithelial cells and gut biopsies of 114 monozygotic (MZ) twins as well as WBC and buccal epithelial cells of 80 dizygotic (DZ) twins using 12K CpG island microarrays. Here we provide the first annotation of epigenetic metastability of approximately 6,000 unique genomic region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
436
4
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(482 citation statements)
references
References 27 publications
31
436
4
11
Order By: Relevance
“…Microarray studies confirmed a decrease in DNA methylation with age, while site‐specific analysis indicated an increase in variability of DNA methylation with age. The latter was first noted in monozygotic twins, and subsequently in unrelated individuals (Fraga et al ., 2005; Martin, 2005; Poulsen et al ., 2007; Kaminsky et al ., 2009; Martino et al ., 2011). These studies also supported the idea that DNA methylation showed reduced stringency in maintenance over the lifespan, resulting in an increase in interindividual variability along with the overall decrease in DNA methylation.…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Microarray studies confirmed a decrease in DNA methylation with age, while site‐specific analysis indicated an increase in variability of DNA methylation with age. The latter was first noted in monozygotic twins, and subsequently in unrelated individuals (Fraga et al ., 2005; Martin, 2005; Poulsen et al ., 2007; Kaminsky et al ., 2009; Martino et al ., 2011). These studies also supported the idea that DNA methylation showed reduced stringency in maintenance over the lifespan, resulting in an increase in interindividual variability along with the overall decrease in DNA methylation.…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
“…Epigenetic drift is now understood to comprise age‐related changes in the epigenome that include those that are acquired environmentally as well as stochastically (Fraga et al ., 2005; Fraga & Esteller, 2007; Kaminsky et al ., 2009; Hannum et al ., 2013; Teschendorff et al ., 2013). Early indications of epigenetic drift were noted in cell culture studies, after the observation that clones of a single cell line became epigenetically divergent upon multiple passages (Humpherys et al ., 2001).…”
Section: Epigenetic Drift Vs the Epigenetic Clock: Two Phenomena Undmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been suggested that age-related methylation alterations depend on genetic effects [9], and another recent study on mother-children pairs reported that meQTL associations were stable over time [12]. Twin studies of the epigenome have been used to estimate methylation heritability [9,13], and higher methylation correlation has been observed in monozygotic (MZ) than dizygotic (DZ) twin pairs [5,14]. However, the change of intra-twin-pair methylation difference over time has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Kaminsky et al mapped differences in DNA methylation at a locus displaying a range of co-twin variability in three types of tissues-white blood cells, buccal epithelial cells, gut (rectum) biopsies and-from MZ and DZ twin pairs using microarrays [Schumacher et al, 2006]. They found a large degree of MZ co-twin DNA methylation variation in all the tissue samples investigated, validating their findings using sodium bisulfite modification based mapping of methylated cytosines in CpG islands [Frommer et al, 1992;Kaminsky et al, 2009]. There are a number of specific epigenetic mechanisms that may alter phenotype, including skewed X-inactivation in FMZ twins, imprinting (differential expression of genes inherited from the mother or father), and DNA methylation, that are discussed below [Gringras and Chen, 2001;Boomsma et al, 2002;Rosa et al, 2008].…”
Section: New Directions In Twin Studies: Epigeneticsmentioning
confidence: 83%